EPIDEMIOLOGY OF DENGUE FEVER AND UTILITY OF DENGUE NS1 ANTIGEN RAPID DIAGNOSTIC POINT OF CARE TEST AT COMBINED MILITARY HOSPITAL MALIR - Abeera Ahmed; Fahim Akhtar; Yasir Rafiq; Nasir Ahmed Rafiq; Shugufta Yousaf; Irfan Najam Sheen (Pakistan Armed Forces Medical Journal, 2020)
Objective: To investigate the incidence and epidemiology of Dengue fever, and to evaluate the utility of NS1 antigen test for the rapid diagnosis of disease at Combined Military Hospital Malir, Karachi.